2015
DOI: 10.15446/ing.investig.v35n3.49498
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the termal decomposition of colombian vacuum residua by termogravimetry

Abstract: Five different Colombian vacuum residues were thermally decomposed in a thermogravimetric analyzer. Three heating rates were employed to heat the sample up to 650 °C. The kinetic analysis was performed by the Coats-Redfern method to describe the non-isothermal pyrolysis of the residua. A reaction model where the reaction order gradually increases from first to second order is proposed, resulting on an excellent agreement of the experimental with the calculated data. The results also indicate that the pyrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Until now, several studies have been reported on the thermal processing of heavy hydrocarbons, , their chemistry, , their kinetics, , and their economies . Depending upon the type of the desirable products of a thermal cracking process, different reaction conditions are employed.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, several studies have been reported on the thermal processing of heavy hydrocarbons, , their chemistry, , their kinetics, , and their economies . Depending upon the type of the desirable products of a thermal cracking process, different reaction conditions are employed.…”
Section: Introductionmentioning
confidence: 99%